Epidemiology & genotyping of rotavirus gastroenteritis and rotavirus associated intussusception in preschool children in central Uttar Pradesh - Sanjeev Kumar Verma; Ashish Wakhlu; Shalini Verma; Sudhir Verma; Andrew S. Day; Nayana P. Nair (Clinical Epidemiology and Global Health)
Objective: Rotavirus (RV) related diarrhea remains a leading cause of mortality in children. This study aimed to establish the burden of RV in preschool children hospitalized for acute gastroenteritis (AGE) at north Indian center and to ascertain the genotypic profile of the RV isolates. Methods: This prospective study was conducted at tertiary care center of north India from 2017 to 2020. Stool samples were collected from children admitted with acute diarrhea. Clinical details were collected using a predesigned proforma. Stored stool samples were analysed for the presence of RV, further for genotyping. Results: Total 1277 eligible children aged <5 year, 968 children were enrolled. Stool samples available from 740 children (76.4 %) were collected and processed. RV was isolated from 219 (29.6 %). Children infected with RV were younger (13.07 ± 9 vs 15.84 ± 17 months, p = 0.023) than those without RV infection. Highest incidence of RV infection during winter months observed. Of 206 samples available for genotyping, 195 had single G and 197 single P types. The most prevalent G and P type combinations were G3P 8 strains, in 51 (23.3 %) children, whereas 16 (7 %) strains had >1 G or P. Twenty-nine children (mean age 6.5 months, 22 male) had presented with intussusception: six were positive for RV. Typable strains detected in two samples were G3 P8 and G1 P4+P6+P8. Conclusion: The study confirms a significant burden of RV among young children admitted with AGE this region of India. G3 P8 was the most common RV strain isolated.